2020
DOI: 10.21203/rs.3.rs-62388/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing Surgical and Conservative Treatment on Achilles Tendon Rupture: A Comprehensive Meta-Analysis of RCTs

Abstract: Background Achilles tendon is the strongest tendon in human and frequently injured mainly in young to middle age active population. Increasing incidence of Achilles tendon rupture (ATR) is still reported in several studies. Surgical repair and conservative treatment are two major management strategy widely adopted in ATR patients but the consensus of optimal treatment strategy is still debated. We aimed at fully reviewing the ATR topic with additional assessments and performed a most comprehensive meta-analysi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…What is interesting from this study also is that of the eight studies that included ‘return to sport’ in their results the authors concluded that there was no difference in timeline between operative and non-operative approaches [18] .…”
Section: Discussionmentioning
confidence: 72%
“…What is interesting from this study also is that of the eight studies that included ‘return to sport’ in their results the authors concluded that there was no difference in timeline between operative and non-operative approaches [18] .…”
Section: Discussionmentioning
confidence: 72%
“…A meta-analysis by Deng et al 7 demonstrated a 9.8% re-rupture rate in nonoperative treatment compared with a 3.7% rate following surgical intervention. She et al 8 also reports a significant reduction in re-rupture but a greater complication rate with surgical intervention including deep vein thrombosis, scar adhesion to underlying tendon, sural nerve injury and infection. Minimally invasive and traditional open Achilles repairs remain controversial as to which approach provides greater patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, from 2010 through 2019, there was decline in operative repair of ATR (18.3%-12.3%, P < .0001); a trend demonstrated in several other studies as well. 1,3,5,18,19 A multicenter, randomized control by Willits et al 8 compared outcomes of ATRs who underwent nonoperative management with functional rehabilitation to operative treatment reporting that all measured outcomes of nonoperative management were acceptable and clinically similar to those of operative treatment while avoiding the complications associated with operative management. In addition, a meta-analysis of randomized trials comparing functional rehabilitation with early range of motion demonstrated that re-rupture rates were equal for operative and nonoperative patients, and the increased risk of having a complication other than a re-rupture in the operative group (risk difference 15.8%) may outweigh the increased risk of re-rupture in the nonoperative group if functional rehabilitation is not an option (risk difference 8.8%).…”
Section: Discussionmentioning
confidence: 99%
“…As more evidence supports nonoperative management with functional rehabilitation for ATRs, the trending characteristics of this evidence has not been elucidated. 3,5,6 While operative repair of the Achilles tendon may decrease the rate of re-rupture, it has also led to more complications compared with nonoperative management, which has been reported to have similar outcomes and less complications. 5,7,8 A study by Ochen et al 7 compared outcomes of operative versus nonoperative treatment of acute ATR demonstrating that operative treatment was associated with a significant reduction in re-rupture rate compared with nonoperative treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation